Attitudes of Vietnamese University students on restrictions of rights and compulsory admissions in patients with severe mental illness – a cross-sectional study - Kemna, Solveig; Nguyen, Van Tuan; Böge, Kerem; Bajbouj, Malek; Bringmann, Max; Weyn-Banningh, Sebastian; Eilinghoff, Luisa; Nguyen, Van Phi; Tuturea, Laura Elisabeth; Le Cong, Thien; Le, Thi Thu Ha; Ta, Thi Minh Tam; et al. (Frontiers in Psychiatry, 2025)
IntroductionThis cross-sectional, explorative study examines university students’ attitudes (n = 610) in Hanoi, Vietnam, toward the rights of psychiatric patients.MethodsMedical students responded to self-report questionnaires investigating their attitudes towards restrictions and compulsory admissions in case of severe mental illness after attending a psychiatry course. Medical students and non-medical students who did not participate in the course served as two control groups.ResultsIn all groups, the majority of students opposed restricting the civil rights of psychiatric patients, but most supported compulsory admissions in certain situations. Medical students who had not attended a psychiatry course were generally more in favor of compulsory admissions compared to those who had attended a psychiatry course and non-medical students. However, when investigating attitudes on compulsory admission in specific scenarios, students that had attended a psychiatry course were more likely to endorse compulsory admissions, except when admission was based on the patient’s family request.DiscussionMedical and psychiatric training seem to encourage more differentiated opinions on the use of compulsory admissions in psychiatric care. Future research, including longitudinal designs and a broader geographical scope, is needed to better understand the impact of psychiatric education in medical studies on attitudes toward mental health.